Prenehanje kolektivne pogodbe z vidika avtonomije strank in uporabe pravil civilnega prava - Kresal Šoltes, Katarina (Delavci in delodajalci, 2011)
In the article the authoress examines issues regarding expiry of collective agreements. Special Collective agreements Act (ZKolP), regulates validity and expiry of the collective agreements, basic conditions for the particular cases of termination and the possibility of the use of collective agreements after the expiry of validity. The authoress examines the slovenian legislationfrom two perspectives. First, which issues related to validity and termination of the collective agreement could be derogated from the law by theparties. Second, which general rules of civil law shall be reasonably applied regarding issues related to collective agreements, which are not regulated by this act or other acts.
Keywords: civilno pravo; delovno pravo; kolektivna pogajanja; kolektivne delovne pogodbe; pogodbeno pravo; prenehanje; prenehanje kolektivne pogodbe; splošna pravila civilnega prava